Adverse pregnancy outcomes and long-term risk of stroke : a Swedish nationwide co-sibling study - Crump, Casey; Sundquist, Jan; Sundquist, Kristina (European Heart Journal, 2025)
The lifelong risk of stroke following adverse pregnancy outcomes, and potential causality, are unknown. This study examined five major adverse pregnancy outcomes and long-term risk of stroke in a large population-based cohort. Methods A national cohort study was conducted of all 2 201 393 women with a singleton delivery in Sweden during 1973–2015, followed up for stroke through 2018. Cox regression was used to determine hazard ratios (HRs) for stroke associated with preterm delivery, small for gestational age, preeclampsia, other hypertensive disorders, and gestational diabetes, adjusting for other maternal factors. Co-sibling analyses assessed for potential confounding by shared familial (genetic or environmental) factors. Results In 48 million person-years of follow-up, 667 774 (30%) women experienced an adverse pregnancy outcome and 35 824 (1.6%) women were diagnosed with stroke. All five adverse pregnancy outcomes were independently associated with long-term increased risks of stroke. With up to 46 years of follow-up, adjusted HRs for stroke associated with specific adverse pregnancy outcomes were: gestational diabetes, 1.86 (95% confidence interval 1.69–2.04); other hypertensive disorders, 1.82 (1.67–1.98); preterm delivery, 1.40 (1.36–1.45); preeclampsia, 1.36 (1.31–1.41); and small for gestational age, 1.26 (1.22–1.29). All HRs remained significantly elevated (1.2- to 2.5-fold) even 30–46 years after delivery. These findings were only partially explained by shared familial factors. Conclusions In a large national cohort, women with any of five adverse pregnancy outcomes had increased risks of stroke up to 46 years after delivery. Women with adverse pregnancy outcomes need early preventive actions and long-term follow-up to reduce their lifelong risk of stroke.
Keywords: Cerebrovascular disorders; Gestational diabetes; Hypertensive disorders of pregnancy; Preeclampsia; Pregnancy complications; Preterm delivery; Small for gestational age; Stroke